AUTOANTIBODIES AND IMMUNOGLOBULINS IN NODAL GENERALIZED OSTEOARTHRITIS - Hilal Sargın; Melek Güngör; Sevim Orkun (Archives of Rheumatology, 2001)
The frequencies of auto antibiodies, including spesific rheumatoid factors, and levels of immunoglobulins were determined in 20 patients with nodal generalized osteoarthritis (NGOA), 20 patients with non-nodal large joint osteoarthritis (LJOA), and 10 non-osteoarthritic controls. Patients with NGOA had a higher frequency of IgG rheumatoid factor compared to LJOA and normal subjects. However, statistical analysis did not reach significance at the group level (p>0.05). IgA levels in the nodal patient group were found to be significantly lower when compared with the other two group but did not significance in statistical analysis. Thyroglobulin autoantibodies levels in the nodal patient group were found be significance higher when compared the control groups (p<0.05). These data support characterization of NGOA as a distinct subset of osteoarthritis, and suggest involvement of immune process in its pathogenesis.